World Workshop on Oral Medicine VII: Immunobiologics for salivary gland disease in Sjögren's syndrome: A systematic review. (29th May 2019) - Gueiros, Luiz A.; France, Katherine; Posey, Rachael; Mays, Jacqueline W.; Carey, Barbara; Sollecito, Thomas P.; Setterfield, Jane; Woo, Sook Bin; Culton, Donna; Payne, Aimee S.; Lodi, Giovanni; Greenberg, Martin S.; et al.
Abstract: Objective: This systematic review evaluated the efficacy of immunobiologics for the management of oral disease in Sjögren's syndrome (SS). Materials and Methods: MEDLINE ®, Embase, Scopus, and the Cochrane Library were searched for evidence on the use of immunobiologics for management of glandular disease in SS. Primary outcomes were xerostomia and salivary gland dysfunction, assessed via visual analogue scales, disease‐specific scales for SS, measurement of salivary flow, ultrasound data, and quality of life measures. Results: Seventeen studies (11 randomized controlled trials and 6 observational studies) met inclusion criteria. Rituximab showed efficacy in improving salivary gland function but not xerostomia. Abatacept showed promise in improving both xerostomia and salivary flow. Belimumab exhibited long‐term improvement of salivary flow and subjective measures. The novel agent CFZ533 improved both disease activity and patient‐reported indexes. Conclusions: There is strong evidence pointing to the efficacy of rituximab in the management of oral disease in SS. Future controlled trials may elucidate the efficacy of belimumab and abatacept. The new drug CFZ533 is a promising alternative for the management of SS and its salivary gland involvement. In considering these agents, the promise of efficacy must be balanced against the harmful effects associated with biologic agents.